PERSPEKTIF MASA DEPAN DAN PENUNDAAN WAKTU TIDUR PADA MAHASISWA - Riska Angelia; Monty P. Satiadarma; Linda Wati (Fakultas Psikologi Universitas Tarumanagara, 2026)
Sleep is one of the needs that must be fulfilled every day for the body to recover and carry out activities with sufficient energy. One aspect of good sleep is adequate sleep duration. However, survey results show 56.3% of students sleep 4-6 hours, with social media use being common activity before bedtime. Bedtime procrastination is intentional postponement of sleep without clear external reason, despite awareness of negative consequences. Bedtime procrastination affects and has an impact on health. Future time perspective serves as a deteerminant of individual behavior, helping them to consider long-term consequences The purpose of this study was to examine the relationship between future time perspective and bedtime procrastination among college students. The study was conducted on individuals who met the criteria of being college students, aged 18-25 years, and had delayed sleep in the past month. This study used a quantitative method with a correlational approach and purposive sampling technique to determine the number of participants, which was 120 participants. The measurement tools used in this study were the Future dimension of the Zimbardo Time Perspective Inventory by Zimbardo and Boyd (1999), adapted by Jonathan (2019), and the Bedtime Procrastination Scale by Kroese et al. (2014), adapted by Christianto and Rostiana (2024). The results of the study showed a negative relationship between future time perspective and bedtime procrastination (r = -0.460). Individuals who do not consider future consequences tend to bedtime procrastination.